ESTABLISHMENT AND STRUCTURE OF CONSTITUTIONAL (AUTHORIZED) COURTS OF THE SUBJECTS OF RUSSIAN FEDERATION - A. G. Gataullin (Russian Journal of Economics and Law, 2008)
The article depicts the process of formation of constitutional control bodies of the Russian Federation subjects. It raises the issue of the need to organize the legislative, executive and judicial authorities at the level of subjects within the Russian Federation.